America in An Arab Mirror - Abdel-Malek, K. author. aut Link
XIII, 152 p.
Keywords: This distinguished anthology presents for the first time in English travel essays by Arabic writers who have visited America in the second half of the century. The view of America which emerges from these accounts is at once fascinating and illuminating, but never monolithic. The writers hail from a variety of viewpoints, regions, and backgrounds, so their descriptions of America differently engage and revise Arab pre-conceptions of Americans and the West. The country figures as everything from the unchanging Other, the very antithesis of the Arab self, to the seductive female, to the Other who is both praiseworthy and reprehensible.